ANALYTIC ELEMENT SOLUTIONS FOR SEEPAGE TOWARDS TOPOGRAPHIC DEPRESSIONS - Kacimov A.R. (My University, 2006)
Point and line singularities are superposed with incident unidirectional saturated and unsaturated flows. The resulting isobars of 3D Laplacian or advective dispersion equation fields model either seepage face dimples and rills on a tilted hillslope or an undulated top of the vadose zone above a stagnant water table. The reconstructed shapes of isobars are conchoidal, i.e. convex-concave. All flow characteristics (drawdowns, velocity and Kirchhoff potential distributions, dimple sizes) are calculated either explicitly or by elementary computer algebra routines. © 2005 Elsevier Ltd All rights reserved.
Keywords: ANALYTIC SOLUTIONS; EVAPORATION; GROUNDWATER; MOISTURE FLOW; SEEPAGE EROSION